INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN KESEHATAN DI BLUD RSUD ENDE - YUSTINA PACIFICA MARIA PASCHALIA (JURNAL KESEHATAN PRIMER, 2016)
Introduction: BLUD Ende Hospital is one of the government agencies that provide health services to the community in Ende. Average visits to BLUD Ende hospital in 2012 as many as 3425 people / month, increasing to 5,094 people / month in 2013 (BLUD Hospital Ende, 2013). With the increasing number of visits, the services required to provide a quality service.The purpose of this study to determine the quality of health care provided in BLUD Ende hospital. Method This research is survey research, design research is quantitative descriptive cross sectional. The data collected in the form of primary data obtained from interviews conductedin order to obtain a detailed picture of respondents' opinions about the satisfaction of health care provided in BLUD Ende hospital. The instrument used for data collection in this study is a questionnaire that was adopted from the minister's decision No. KEP/ 25 / M.PAN / 2/2004 about General Guidelines for Preparation of Public Satisfaction Index Services in Government Agencies Unit . The data were analyzed descriptively. Result: The results showed that BLUD Ende Hospital Community service Satisfaction Index is 2.98; After converted obtained from the value of the index base value x = 2.98 x 25 = 74.55 with the quality of service is B. Conclusion: From these results it can be concluded that the performance of units service in BLUD Ende hospital is "Good". Therefore it is advisable to maintain and improve the quality of services for Ende’s society, in order to enhance the value of satisfaction of the user, specially community health services in BLUD Ende hospital, thus the performance of the service unit can be increased as well.